High levels of Bifidobacteriaceae are associated with the pathogenesis of Parkinson’s disease - Zuo, ShuJia; Wang, HaiJing; Zhao, Qiang; Tang, Jie; Wang, Min; Zhang, Yu; Sang, Ming; Tian, Jing; Wang, Puqing (Frontiers in Integrative Neuroscience, 2023)
Background The diagnosis of Parkinson’s disease (PD) is complex and there are no biomarkers for early identification. Many studies have reported altered gut microbiota in patients with PD compared with healthy individuals. However, results from previous studies vary across countries. Aims The aim of this study was to identify gut microbiota biomarkers that could be used as a marker for the diagnosis of PD. Methods Firstly, the differential gut microbiota was obtained by meta-analysis, and then the results of meta-analysis were validated through metagenomic cohort. Finally, the ROC curve was drawn based on the metagenomic validation results. Results The meta-analysis showed a lower relative abundance of Prevotellaceae (p < 0.00001) and Lachnospiraceae (p = 0.002), and a higher of Ruminococcaceae (p < 0.00001), Christensenellaceae (p = 0.03), Bifidobacteriaceae (p < 0.00001), and Verrucomicrobiaceae (p = 0.23) in patients with PD. Only Bifidobacteriaceae was also at high levels in the validation cohort of the metagenome. Meanwhile, three species from the Bifidobacteriaceae, including Scardovia_inopinata (p = 0.022), Bifidobacterium_dentium (p = 0.005), and Scardovia_wiggsiae (p = 0.024) were also high. The ROC curve showed that the three species (71.2%) from Bifidobacteriaceae had good predictive efficiency for PD. Conclusion Elevated Bifidobacteriaceae may be associated with PD. Elevated three species from the Bifidobacteriaceae, including Scardovia_inopinata, Bifidobacterium_dentium and Scardovia_wiggsiae may provide new potential biomarkers for the diagnosis of PD.